Slow Violence, Sacrifice, and Survival: Environmental Catastrophe as (Eco)Feminist Freedom in Zora Neale Hurston’s Their Eyes Were Watching God - Nelson, Holly (Lagoonscapes)
In Their Eyes Were Watching God, Zora Neale Hurston makes visible ‘slow violence’ and ‘sacrifice zones’ to establish a feminist future for her protagonist, Janie. The novel shows a fictional rendering of the 1928 Okeechobee Hurricane, a storm that Janie survives. In this article, the Author contends that Janie’s survival of the storm – her surmounting of ‘slow violence’ and bypassing of sacrifice in the ‘sacrifice zone’ – emboldens her to overcome patriarchal violence at the novel’s conclusion. Hurston expresses a gendered writer-activism critiquing not only environmental racism, but the intersectional battles of Black women experiencing environmental and patriarchal violence.